Spatiotemporal Variations of the 90Sr in the Southern Part of the Baltic Sea over the Period of 2005–2010 - Michał Saniewski (The Scientific World Journal)
The Baltic Sea is one of the most contaminated seas by the radioactive isotope of strontium in the world; therefore the activity of 90Sr is regularly controlled. Due to that fact, seawater samples for 90Sr determination were collected at 16 stations located in the southern Baltic Sea between 2005 and 2010. In this period average activity of 90Sr was 7.8 Bq m−3 and varied within the range from 3.0 Bq m−3 to 11.9 Bq m−3. Because the higher activity of 90Sr was measured in the Baltic Sea than in the North Sea and rivers, inflows from the North Sea and the riverine runoff decreased 90Sr activity in the Baltic Sea. The average 90Sr activity in the bottom water along the offshore profile was 18% lower than that in the surface water and it was caused by an inflow of salt water from the North Sea. In the Vistula River mouth the average activity of 90Sr in the surface water was about 15% lower than the average activity in the bottom waters. Coastal areas, relatively shallow with good mixing condition in the water column, were characterized by low variability in 90Sr activity.